Qualidade físico-química, microbiológica e detecção de soro lácteo por cromatografia líquida de alta eficiência em bebidas lácteas fermentadas - Elisa Helena Paz Andrade (2010)
Physical-chemical and microbiological quality of fermented milk beverages sold at big markets from Belo Horizonte, Minas Gerais state, Brazil were evaluated. Gerber and Roese-Gottlieb methods to determine the fat content were compared. Cheese whey level and CMP index of fermented milk beverages added with four levels of cheese whey (0, 10, 20, and 40%) and stored at 8-10oC for 0, 7, 14 and 21 days were determined by HPLC on a gel permeation column. Also, the interference of the starter culture and the storage time on the detection of cheese whey and CMP were investigated. These samples showed satisfactory microbiological quality. The counts of lactic acid bacteria were higher than the minimum required by the Brazilian legislation. The means of protein content of all products were higher than the minimum required by the Brazilian legislation. There was no difference (P>0.05) between means of fat content using both Gerber and Roese-Gottlieb methods. Refrigerated storage up to 21 days did not affect (P>0.05) cheese whey and CMP amounts in milk (0% of cheese whey) and in fermented milk beverages added with 10 and 20% of cheese whey (P>0.05). However, cheese whey and CMP amounts were higher than expected (P<0.05) in fermented milk beverage added with 40% of cheese whey and stored for 21 days